Medical Student Appraisal - Khalifian, S.; Markman, T.; Sampognaro, P.; Mitchell, S.; Weeks, S.; Dattilo, J. (Applied Clinical Informatics, 2013)
Background: The rapidly growing industry for mobile medical applications provides numerous smartphone resources designed for healthcare professionals. However, not all applications are equally useful in addressing the questions of early medical trainees.Methods: Three popular, free, mobile healthcare applications were evaluated along with a GoogleTM web search on both AppleTM and AndroidTM devices. Six medical students at a large academic hospital evaluated each application for a one-week period while on various clinical rotations.Results: GoogleTM was the most frequently used search method and presented multimedia resources but was inefficient for obtaining clinical management information. EpocratesTM Pill ID feature was praised for its clinical utility. MedscapeTM had the highest satisfaction of search and excelled through interactive educational features. MicromedexTM offered both FDA and off-label dosing for drugs.Discussion: GoogleTM was the preferred search method for questions related to basic disease processes and multimedia resources, but was inadequate for clinical management. Caution should also be exercised when using GoogleTM in front of patients. MedscapeTM was the most appealing application due to a broad scope of content and educational features relevant to medical trainees. Students should also be cognizant of how mobile technology may be perceived by their evaluators to avoid false impressions.Citation: Dattilo J, Khalifian S, Markman T, Sampognaro P, Mitchell S, Weeks S. Medical student appraisal: searching on smartphones. Appl Clin Inf 2013; 4: 53–60http://dx.doi.org/10.4338/ACI-2012-10-CR-0047
Keywords: Application; mobile health; electronics; smartphone